Contemporary Pediatric Hematology and Oncology - Zakaria, Marwa; Hassan, Tamer (IntechOpen, 2019)
Contemporary Pediatric Hematology and Oncology covers many aspects of research and patient management within the area of blood disorders and malignant diseases in children. Blood diseases are a distinctive group of inherited and acquired, benign and malignant, acute and chronic disorders with diverse incidence, etiology, pathogenesis, and prognosis. Of interest are clinical studies as well as basic and translational research reports regarding pathogenesis, genetics, molecular diagnostics, pharmacology, molecular targeting, standard and novel therapies for the most common blood disorders, and childhood cancer. This book intends to provide the reader with a comprehensive overview of today's practices and tomorrow's possibilities regarding the most important pediatric hematological and oncological diseases.